(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines the role of information and communication technologies (ICT) in the formation of professional competence among specialists in the field of sports. The study highlights how ICT tools and platforms contribute to the acquisition of theoretical knowledge, the development of practical skills, and the improvement of professional communication. Particular attention is paid to the integration of digital learning resources, multimedia training programs, and interactive platforms into the curriculum of higher educational institutions specializing in physical culture and sports. The paper also analyzes the pedagogical, methodological, and technological aspects of ICT application, emphasizing their impact on the efficiency of teaching, learning motivation, and the enhancement of student autonomy. The results show that the implementation of ICT in sports education contributes to the modernization of teaching practices and provides a foundation for the development of competitive specialists capable of responding to the requirements of the modern labor market.